Islamic tareekh ki suchi khaniyan - Zaidi Nazar (Pakistan, 2005)
Islamic Tareekh Ki Suchi Khaniyan offers a collection of true stories from Islamic history, providing insightful lessons on faith, perseverance, and moral values.